On blindness of several ElGamal-type blind signatures - Babueva, A. A.; Akhmetzyanova, L. R.; Alekseev, E. K.; Taraskin, O. G. (Прикладная дискретная математика)
Blind signature schemes are the essential element of many e-cash and e-voting systems. Anonymity in such systems is ensured through the blindness property of the signature schemes. We discuss the blindness property and analyze several ElGamal-type blind signature schemes regarding this property. We present effective attacks violating blindness on three schemes.